2021
DOI: 10.3389/fphys.2021.682482
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide Exacerbates Renal Inflammation and Fibrosis in Rats With Diabetic Kidney Disease

Abstract: The gut microbiota plays a pivotal role in the onset and development of diabetes and its complications. Trimethylamine N-oxide (TMAO), a gut microbiota-dependent metabolite of certain nutrients, is associated with type 2 diabetes and its complications. Diabetic kidney disease (DKD) is one of the most serious microvascular complications. However, whether TMAO accelerates the development of DKD remains unclear. We tested the hypothesis that TMAO accelerates the development of DKD. A high-fat diet/low-dose strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 72 publications
5
52
0
1
Order By: Relevance
“…Several studies have investigated the role of TMAO in fibrosis development in various diseases [17,19,[29][30][31]. In the kidneys, renal fibrosis leads to nephron loss and progressively declined renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of TMAO in fibrosis development in various diseases [17,19,[29][30][31]. In the kidneys, renal fibrosis leads to nephron loss and progressively declined renal function.…”
Section: Discussionmentioning
confidence: 99%
“…TMAO accelerates the development of diabetic kidney disease (DKD) in a high-fat diet/low-dose streptozotocin-induced diabetes rat model. By feeding drinking water containing TMAO, the DKD rats showed exacerbated kidney dysfunction accompanied with renal fibrosis ( Fang et al, 2021 ). A structural analog of choline, 3,3-dimethyl-1-butanol (DMB), was shown to reduce TMAO levels in mice fed by a high-choline or l -carnitine diet ( Wang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with the in vitro study by Peruchetti et al [ 23 ]. An earlier in vivo study showed that rats with diabetes and diabetic kidney disease (DKD) fed with a high-fat diet, had increased urine protein and urine albumin levels compared to control rats [ 33 ]. Rats with DKD fed with the same diet, but with TMAO supplementation in their drinking water, exhibited higher urine protein and urine albumin levels compared to DKD rats with only a high-fat diet [ 33 ].…”
Section: Discussionmentioning
confidence: 99%